Ковальська майстерня ХIII—XIV ст. в Поворсклі - Пуголовок, Ю.О. (Археологія, 2017)
Публікуються залишки виробничої споруди з Глинського археологічного комплексу. Виявлені знахідки доповнюють джерельну базу з вивчення ковальського ремесла у післямонгольський час на території Дніпровського Лівобережжя. The article presents the remains of production facilities discovered during excavations on the territory of Hlynske archaeological assemblage. The object is interpreted as the 13th—14th centuries smithy. This is indicated by the construction features of a structure, the heating facilities, traces of a craftsman’s place, as well as findings of finished, half-finished, and waste products. The conclusions on the objects’ function resulting from the excavations are also confirmed by the analysis of charcoal. On a whole, the assemblage contained about 60 different items and workpieces, as well as 90 units of production waste. Building features and findings’ specificity indicate a workplace of a universal blacksmith. An assemblage studied extends and complements the database for the study the blacksmith in the post-Mongolian period on the Dnipro River left bank region. В статье публикуются остатки производственного сооружения, обнаруженного во время раскопок на территории Глинского археологического комплекса. Объект интерпретируется как кузница XIII—XIV вв. На это указывают конструктивные особенности постройки, наличие теплотехнического сооружения, следы рабочего места мастера, а также находки готовой продукции, заготовок и отходов производства. Выводы о назначении объекта, полученные в результате раскопок, подтверждаются также анализом древесного угля. В целом, в комплексе выявлены около 60 разнообразных предметов и заготовок, а также около 90 единиц отходов производства. Особенности постройки, а также специфика находок указывают на рабочее место здесь универсального кузнеца. Исследованный комплекс расширяет и дополняет базу данных по изучению кузнечного ремесла в послемонгольское время на территории Днепровского Левобережья.